RANCANG BANGUN TIMBANGAN DIGITAL KOPI BERBASIS INTERNET OF THINGS UNTUK PENCATATAN DAN OTOMATISASI PENGURANGAN STOK BAHAN - Wicaksono, Ferdiansyah; Maulana, Eka; Nurussa’adah, n/a (Jurnal Mahasiswa TEUB, 2024)
The development of the coffee industry in Indonesia is growing rapidly. In the coffee industry, the quality and consistency of coffee flavor is very important where the right proportion of coffee and other additives is a major factor. In addition, operational efficiency in the coffee industry is also important to maintain competitiveness and optimal profits. This can be achieved by managing material stock and recording accurate weighing results so that stock opname activities are needed. One of the coffee shops that implement stock opname in Malang City is Toko Kopi Jaya. The calculation of existing material stock at Toko Kopi Jaya is currently still carried out in a conventional way where the basic ingredients of drinks such as espresso and milk are weighed manually at the end of operating hours. Manual calculations cause problems, such as errors in recording the results of weighing the stock of ingredients. The Internet of Things (IoT) can provide many innovative solutions to improve efficiency in various industries. In the context of the coffee industry, the application of IoT technology to digital scales can provide an effective solution to overcome the problem of inefficient calculation of the current stock of ingredients. The design of IoT-based coffee digital scales was successfully carried out for the automation of material stock reduction using the main components in the form of load cell sensors, HX711 modules, LCDs, and push buttons controlled by ESP8266. The reading data from the load cell sensor is received by ESP8266 and sent to Google Sheet. The load cell sensor used in this IoT-based digital scale has an accuracy rate of 99.964% and the system has an accurate rate of 99.7%. The integration system of IoT-based digital coffee scales with Google Sheet via Wi-Fi connection allows real-time recording of material usage and automatic reduction of material stock. Keyword: scale, Internet of Things, Stock Opname